2008
DOI: 10.1128/iai.00467-08
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of the Response Regulator Rrp2 in the Infectious Cycle of Borrelia burgdorferi

Abstract: Alteration of surface lipoprotein profiles is a key strategy that the Lyme disease pathogen, Borrelia burgdorferi, has evolved to be maintained within its enzootic cycle between arthropods and mammals. Accumulated evidence indicates that the central regulatory pathway controlling differential gene expression by B. burgdorferi is the RpoN-RpoS pathway (the 54 -S sigma factor cascade). It was previously shown that activation of the RpoN-RpoS pathway is controlled by Rrp2, a two-component response regulator and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
156
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(165 citation statements)
references
References 60 publications
8
156
1
Order By: Relevance
“…Abundant evidence has emerged indicating that the Rrp2/RpoN/RpoS pathway serves as a master regulator of the genetic programs required for infection of the mammalian host (19,35,51,(81)(82)(83). The imaging studies presented here provide a structural framework for interpreting the transcriptional events mediated by RpoS during tick-to-mammal transmission.…”
Section: Figurementioning
confidence: 92%
“…Abundant evidence has emerged indicating that the Rrp2/RpoN/RpoS pathway serves as a master regulator of the genetic programs required for infection of the mammalian host (19,35,51,(81)(82)(83). The imaging studies presented here provide a structural framework for interpreting the transcriptional events mediated by RpoS during tick-to-mammal transmission.…”
Section: Figurementioning
confidence: 92%
“…I. scapularis nymphs or larvae (obtained from the Tick Rearing Facility at Oklahoma State University, Stillwater, OK) were artificially infected with various strains of Bb by using a microinjection technique (11,43) or an immersion method (30) (see SI Methods). After infection, ticks were fed to repletion on separate naïve C3H/HeN mice.…”
Section: Sensitivity Of Bb To Rosmentioning
confidence: 99%
“…It is now well established that outer surface (lipo)protein C (OspC), OspA/B, decorin-binding protein B/A (DbpB/A), PncA, and BptA are required by Bb for efficient infection of ticks or mammalian hosts (4)(5)(6)(7)(8)(9)(10). It is also generally accepted that the recently discovered Rrp2-RpoN ( 54 )-RpoS ( S ) regulatory pathway plays prominently in Bb's virulence expression (11)(12)(13)(14).…”
mentioning
confidence: 99%
“…A central regulatory pathway comprising Rrp2-RpoN-RpoS has been characterized as regulating outer surface protein C (OspC), decorin binding protein A (DbpA), fibronectin binding protein BBK32, and several other borrelial determinants involved in various pathogenic processes (11, 17-20, 41, 88). Mutations in one or more of these regulators have also been characterized as having significant global effects on the transcriptional levels of a large number of ORFs in B. burgdorferi (12,17,20,31,61). Recently, it has also been shown that inactivation of ospAB constitutively activates the Rrp2-RpoNRpoS pathway, indicating mechanisms that are unique to B. burgdorferi and to its survival strategies in the tick vector and mammalian hosts (40).…”
mentioning
confidence: 99%